NEUTRACEUTICALS: ROLE OF NATURAL MOLECULES IN PHARMACOTHERAPY - DR.D.M.RAVICHAND (International Journal of Pharma and Bio Sciences, 2015)
In recent years there is a growing interest in neutraceuticals which provide health benefits and acts as an alternative treatment to the modern medicine. The ability of neutraceuticals to influence chronic diseases like diabetes, different types of cancers, etc. should be recognized as an enormous opportunity in their treatment by using natural molecules. These neutraceuticals are the medicinal food that not only enhances the human health but modulates immunity and intern prevents and also helps in curing certain specific diseases. Neutraceuticals may range from natural diets, herbal and polyherbal products to genetically engineered foods and also the processed products such as cereals, soups and beverages. These neutraceuticals play a vital role in future therapeutic development. By employing the neutraceuticals in the armamentarium of pharmacotherapy it is possible to reduce or even eliminate the need for conventional medications, which intern helps in reducing the chances of the associated adverse effect and thus promoting the quality of life. Pharmaceutical and nutritional companies are aware of the monetary success taking advantage of the more health-seeking consumers and the changing trends in the therapeutic interventions resulting in value-added products aimed at better health for tomorrow. The neutraceuticals revolution will lead us into a new direction of medicine and health. Attempts were made to review the neutraceuticals as an alternative treatment for different types of disease. Primarily which is aimed at cost effective treatment with less or no side effects.